(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
The Chinatown area, recognized as the hub of commerce and residence for the Chinese community, spans across nearly all Indonesian cities, including Malang City. Pasar Besar Street is a main access route for visitors exploring Chinatown in Malang City. During the British colonial era, the implementation of the five-foot way policy, which mandated the construction of sidewalks along roadsides, significantly influenced this area’s physical and social landscape. This concept connects public and private spaces, facilitating social interactions and economic activities, known as the public-private interface. This research employs a qualitative-descriptive approach to examine the characteristics of the public-private interface, focusing on building frontages and street spaces. The findings unveil a variety of public-private interface typologies, including impermeable, direct, and setback types, which can adapt to other typologies to accommodate user behavior and the surrounding environment. This study holds the potential to offer insights into how the public-private interface shapes the identity and sustainability of urban areas.